Pengembangan Inovasi UMKM Wong Djamoe Di Desa Pulosari Kabupaten Jombang - Mayga Putri Shabella; Yogi Pratama Putra; Diana Hertati; Taysa Adila (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Jamu is a traditional drink which is one of the heritages, by utilizing spices that grow in Indonesia. This “Wong Djamoe” product is an innovative product of herbal medicine which is marketed in the form of yogurt and ice cream which has traditional herbal flavors such as ginger, kencur, turmeric, and temulawak flavors. However, in terms of MSME branding, this is a little lacking, namely the lack of identification from the production house and in terms of packaging. The general purpose of this community service activity carried out by UPN "Veteran" East Java students is to help develop product innovation by carrying out product branding and digital marketing for UMKM Wong Djamoe in Pulosari Village. The dedication method carried out by the author begins with visits to partners to carry out FGD (Focus Group Discussion) activities with herbal MSMEs practitioners. The results of the FGD, product innovation carried out is a process of developing new products with the aim of meeting consumer needs, increasing competitiveness, and creating added value. Because in the current era of rapid technological development, it encourages MSME actors to adapt in developing their business by utilizing existing technology. So at this stage activities were carried out to create an MSME website and take product photos again in Pulosari Village which displayed all MSME products in the village along with information. Jamu is a traditional drink which is one of the heritages, by utilizing spices that grow in Indonesia. This “Wong Djamoe” product is an innovative product of herbal medicine which is marketed in the form of yogurt and ice cream which has traditional herbal flavors such as ginger, kencur, turmeric, and temulawak flavors. However, in terms of MSME branding, this is a little lacking, namely the lack of identification from the production house and in terms of packaging. The general purpose of this community service activity carried out by UPN "Veteran" East Java students is to help develop product innovation by carrying out product branding and digital marketing for UMKM Wong Djamoe in Pulosari Village. The dedication method carried out by the author begins with visits to partners to carry out FGD (Focus Group Discussion) activities with herbal MSMEs practitioners. The results of the FGD, product innovation carried out is a process of developing new products with the aim of meeting consumer needs, increasing competitiveness, and creating added value. Because in the current era of rapid technological development, it encourages MSME actors to adapt in developing their business by utilizing existing technology. So at this stage activities were carried out to create an MSME website and take product photos again in Pulosari Village which displayed all MSME products in the village along with information.